3D geometric modelling of discontinuous fibre composites using a force-directed algorithm. (July 2017) - Harper, LT; Qian, CC; Luchoo, R; Warrior, NA
A geometrical modelling scheme is presented to produce representative architectures for discontinuous fibre composites, enabling downstream modelling of mechanical properties. The model generates realistic random fibre architectures containing high filament count bundles (>3k) and high (∼50%) fibre volume fractions. Fibre bundles are modelled as thin shells using a multidimensional modelling strategy, in which fibre bundles are distributed and compacted to simulate pressure being applied from a matched mould tool. Finite element simulations are performed to benchmark the in-plane mechanical properties obtained from the numerical model against experimental data, with a detailed study presented to evaluate the tensile properties at various fibre volume fractions and specimen thicknesses. Tensile modulus predictions are in close agreement (less than 5% error) with experimental data at volume fractions below 45%. Ultimate tensile strength predictions are within 4.2% of the experimental data at volume fractions between 40 and 55%. This is a significant improvement over existing 2D modelling approaches, as the current model offers increased levels of fidelity, capturing dominant failure mechanisms and the influence of out-of-plane fibres.